Can Blood-Based Prostate Cancer Screening Be a Win-Win Situation for Insurance Companies, the Healthcare Industry, and Patients? - Pandya, Jigar (Digital Repository of Theses, 2025)
This research investigates the potential of blood-based prostate cancer screening, particularly multi-cancer early detection (MCED) technologies, as a value-creating intervention for insurers, patients, and the broader healthcare industry in India. The study was driven by the growing economic and clinical burden of late-stage prostate cancer and the emerging promise of liquid biopsy-based approaches to transform preventive care. A mixed-methods design was employed, combining a cost-benefit model with qualitative and quantitative data from a survey of insurance industry professionals. The cost-benefit analysis quantified financial savings for insurers under different sensitivity scenarios, while the survey captured stakeholder perspectives on adoption barriers, regulatory challenges, and broader industry implications. The results demonstrated that insurers could achieve substantial financial savings by integrating blood-based prostate cancer screening into policy-linked health checkups, with projected savings ranging from ₹67 lakhs at 70% sensitivity to over ₹2 crores at 100% sensitivity. From a patient perspective, the findings underscored advantages such as reduced invasiveness, improved compliance, and earlier detection compared to conventional screening modalities. However, multiple obstacles emerged, including high upfront implementation costs, regulatory ambiguity, lack of actuarial models for preventive diagnostics, and infrastructure gaps within provider and laboratory networks. The study further highlighted that regulatory uncertainty and unclear reimbursement pathways remain central deterrents to adoption. Broader implications for providers, laboratories, and med-tech firms include the need for training, standardization, and alignment of innovation with payer requirements. Stakeholders emphasized the importance of policy reforms that balance innovation with oversight, including clearer approval pathways, standardized reimbursement models, and collaborative pilot programs. In conclusion, blood-based prostate cancer screening presents a promising win-win opportunity for insurers, patients, and the healthcare industry. Yet, realizing this potential will require coordinated policy interventions, regulatory clarity, and multi-stakeholder collaboration to overcome barriers and enable sustainable integration into India’s healthcare ecosystem.